Effects of Nigella sativa and Lepidium sativum on Cyclosporine Pharmacokinetics - F. I. Al-Jenoobi (BioMed Research International, 2013)
The present study was conducted to investigate the effects of Nigella sativa and Lepidium sativum on the pharmacokinetics of cyclosporine in rabbits. Two groups of animals were treated separately with Nigella sativa (200 mg/kg p.o.) or Lepidium sativum (150 mg/kg p.o.) for eight consecutive days. On the 8th day, cyclosporine (30 mg/kg p.o.) was administered to each group one hour after herbal treatment. Blood samples were withdrawn at different time intervals (0.0, 0.5, 1.0, 1.5, 2.0, 3.0, 4.0, 6.0, 8.0, 12, and 24 hrs) from marginal ear vein. Cyclosporine was analyzed using UPLC/MS method. The coadministration of Nigella sativa significantly decreased the Cmax and AUC0-∞ of cyclosporine; the change was observed by 35.5% and 55.9%, respectively (P≤0.05). Lepidium sativum did not produce any significant change in Cmax of cyclosporine, although its absorption was significantly delayed compared with control group. A remarkable change was observed in Tmax and AUC0-t of Lepidium sativum treated group. Our findings suggest that concurrent consumption of Nigella sativa and Lepidium sativum could alter the pharmacokinetics of cyclosporine at various levels.